An overview of the international regulatory frameworks that influence the conservation and use of underutilized plant species - Chishakwe, N.E.; Genetic Resources Policy Initiative; Global Facilitation Unit for Underutilized Species (2008)
”An overview of the international regulatory frameworks that influence the conservation and use of underutilized plant species” was prepared by the Global Facilitation Unit for Underutilized Species (GFU), in cooperation with the Genetic Resources Policy Initiative (GRPI). This publication is an effort of the GFU to set the scene and provide an instrument for policy and decision makers. The principal objective of this study is to review and analyze some of the important international policy instruments that affect the conservation and extended use of underutilized plant species. It examines international treaties and conventions and, where necessary, some regional treaties and regulatory instruments. This is done with the aim of identifying gaps or constraints that impede the conservation and extended use of underutilized plant species and also to highlight opportunities which these legal frameworks offer to enhance the conservation and greater use of these species. A separate publication ”The role of policy in the conservation and extended use of underutilized plant species: a cross-national policy analysis” is available in hardcopy or on line and emphasizes on the impact of national policies on the use of currently underutilized plant species and is based on the analysis of existing policies in eight different countries. The policy studies commissioned and carried out by the GFU are to be found here.